The Role of the Carnitine/Organic Cation Transporter Novel 2 in the Clinical Outcome of Patients With Locally Advanced Esophageal Carcinoma Treated With Oxaliplatin - Sun, Dongfeng; Chen, Qingfa; Gai, Zhibo; Zhang, Fengxia; Yang, Xiaoqing; Hu, Wensi; Chen, Chengyu; Yang, Guangjie; Hörmann, Severin; Kullak-Ublick, Gerd. A.; Visentin, Michele (Frontiers in Pharmacology, 2021)
Esophageal cancer is the ninth most common malignancy worldwide, ranking sixth in mortality. Platinum-based chemotherapy is commonly used for treating locally advanced esophageal cancer, yet it is ineffective in a large portion of patients. There is a need for reliable molecular markers with direct clinical application for a prospective selection of patients who can benefit from chemotherapy and patients in whom toxicity is likely to outweigh the benefit. The cytotoxic activity of platinum derivatives largely depends on the uptake and accumulation into cells, primarily by organic cation transporters (OCTs). The aim of the study was to investigate the impact of OCT expression on the clinical outcome of patients with esophageal cancer treated with oxaliplatin. Twenty patients with esophageal squamous cell carcinoma (SCC) were prospectively enrolled and surgical specimens used for screening OCT expression level by western blotting and/or immunostaining, and for culture of cancer cells. Sixty-seven patients with SCC who received oxaliplatin and for whom follow-up was available were retrospectively assessed for organic cation/carnitine transporter 2 (OCTN2) expression by real time RT-PCR and immunostaining. OCTN2 staining was also performed in 22 esophageal adenocarcinomas. OCTN2 function in patient-derived cancer cells was evaluated by assessing L-carnitine uptake and sensitivity to oxaliplatin. The impact of OCTN2 on oxaliplatin activity was also assessed in HEK293 cells overexpressing OCTN2. OCTN2 expression was higher in tumor than in normal tissues. In patient-derived cancer cells and HEK293 cells, the expression of OCTN2 sensitized to oxaliplatin. Patients treated with oxaliplatin who had high OCTN2 level in the tumor tissue had a reduced risk of recurrence and a longer survival time than those with low expression of OCTN2 in tumor tissue. In conclusion, OCTN2 is expressed in esophageal cancer and it is likely to contribute to the accumulation and cytotoxic activity of oxaliplatin in patients with esophageal carcinoma treated with oxaliplatin.